KAJIAN COIL STANDART DAN RACING TERHADAP KOMSUMSI BAHAN BAKAR PADA MESIN 125 CC - PASARIBU, SABAR (JTIK (Jurnal Teknik Informatika Kaputama), 2019)
This study aims to determine the effect of coil voltage on fuel consumption in supra x 125. Coil is used as a modifier of low voltage current into high voltage to produce sparks on spark plugs. and is expected to get various benefits, including the use of fuel so as not to be wasteful. In this study, experimental research methods were used. The research tools of multitester, measuring cup, gasoline material results in carrying out this research are the average amount of fuel for coil racing 1.50 ml / minute for standard coil 1.64 ml / minute shows higher the coil racing voltage is a lot of fuel that is hugged to process in the combustion chamber compared to standard coil does not require the amount of fuel for the process in the combustion chamber use standard coil voltage so that the use of fuel is not wasteful.